Pediatric robot-assisted extravesical ureteral reimplantation (revur) in simple and complex ureter anatomy: Report of a multicenter experience. Issue 1 (February 2023) - Esposito, Ciro; Masieri, Lorenzo; Fourcade, Laurent; Ballouhey, Quentin; Varlet, Francois; Scalabre, Aurelien; Castagnetti, Marco; El Ghoneimi, Alaa; Escolino, Maria
Summary: Background: Robot-assisted extravesical ureteral reimplantation (REVUR) is a well established approach for surgical treatment of pediatric vesicoureteral reflux (VUR). However, further evidence is needed to confirm its efficacy even in case of complex anatomy. Objective: This study aimed to further confirm the evidence that REVUR is safe and effective in both simple and complex ureter anatomy. Study design: The charts of all patients with VUR, who received REVUR in 6 different institutions over a 5-year period, were retrospectively reviewed. Patients with both simple and complex ureter anatomy were included. Patient demographics, surgical variables, and post-operative results were assessed. VUR resolution was defined as either being resolved VUR on voiding cystourethrogram (VCUG) or clinically without symptoms during the follow-up. Results: Fifty-seven patients with median age of 6.9 years (range 4.5–12), receiving REVUR in the study period, were included. Eighteen (31.6%) patients had complex anatomy and included prior failed endoscopic injection (n = 13), complete ureteral duplication (n = 2), periureteral diverticulum (n = 2), ectopic megaureter requiring dismembering (n = 1). The median operative time was 155 min for unilateral and 211.5 min for bilateral repairs. The clinical + radiographic VUR resolution rate was 96.5%. Post-operative complications (Clavien 2) included urinary retention following bilateral repair (n = 5, 8.7%), febrile urinary tract infection (UTI) (n = 6, 10.5%) and gross hematuria (n = 3, 5.2%). Comparative analysis between simple and complex cases showed that REVUR was faster in simple cases in both unilateral [p = 0.002] and bilateral repair [p = 0.001] and post-operative urinary retention was more frequent in simple cases [p = 0.004] and in patients with pre-operative bowel and bladder dysfunction (BBD) [p = 0.001] (Table). Discussion: This series confirmed that the robot-assisted technique was feasible even in cases with complex anatomy using some technical refinements, that justified the longer operative times in both unilateral and bilateral cases. An interesting finding of this study was the correlation emerged between BBD and risk of post-operative urinary retention and VUR persistence. Our results also excluded any significant correlation between complex cases and risk of post-operative urinary retention. The main study limitations included the retrospective and nonrandomized design, the small number of cases and the arbitrary definition of complex anatomy. Conclusion: REVUR was safe and effective for management of VUR in both simple and complex ureter anatomy. Complex REVUR required slightly longer operative times, without significant differences in post-operative mordidity and success rates. Aside from complex anatomy, BBD emerged as the main risk factor associated with surgical failure and post-operative morbidity. Summary Table Comparative analysis between simple and complex REVUR. Summary Table Parameter Simple REVUR n = 39 Complex REVUR n = 18 p value Median OT, min (range)       Unilateral 140.8 (115–165) 169.2 (110–270) 0.002 Bilateral 160 (120–200) 263 (195–290) 0.001 VUR resolution, n (%) 38 (97.4) 17 (94.4) 0.20 VUR persistence, n (%) 1 (2.6) 0 0.06 VUR persistence + contralateral de novo VUR, n (%) 0 1 (5.6) 0.55 Post-operative complications Urinary retention, n (%) 4 (10.3) 1 (5.6)   Unilateral, n (%) 0/23 0/15 0.004 Bilateral, n (%) 4/16 (25) 1/3 (33.3) 0.78 Febrile UTIs, n (%) 4 (10.3) 2 (11.2) 0.33 Ureteral obstruction, n (%) 0 0   Gross hematuria, n (%) 0 2 (11.2) 0.88 OT = operative time; VUR = vesicoureteral reflux; UTIs=urinary tract infections.reflux; UTIs=urinary tract infections.